A Comprehensive Coordinator Supported Hepatitis C Virus Testing and Linkage to Treatment Program at Kaiser Permanente Mid-Atlantic States - Mary Cabell Jonas; Kevin Rubenstein; Eric Watson; Sundeep Basra; Michael Horberg (Viruses, 2021)
Since 2020, the US Preventive Services Taskforce has recommended expanding hepatitis C virus (HCV) screening to include ages 18−79, in addition to baby boomers (born 1945−1965) and those at-risk for hepatitis C virus. This retrospective cohort analysis compared patients (18 years and above) tested for HCV through usual care versus a coordinator-supported program (HCV pathway) during 2015−2018 within Kaiser Permanente Mid-Atlantic States (KPMAS). In total, 131,176 patients were tested through the HCV pathway and 128,311 through usual care (non-standardized testing). Of those tested, 1.6% (HCV pathway) and 0.5% (usual care) had chronic HCV. Of those with chronic HCV, more patients tested within the HCV pathway completed hepatic transient elastography (82.6% HCV pathway vs. 45.6% usual care; p < 0.001) and a gastroenterology visit (72.2% HCV pathway vs. 46.5% usual care; p < 0.001), and had filled prescriptions for treatment (56.5% HCV pathway vs. 40.3% usual care; p < 0.001). The median time to complete each step was shorter for those tested through the HCV pathway (hepatic transient elastography (26 vs. 118 days), gastroenterology visit (63 vs. 131 days), and prescription fill (222 vs. 326 days)). More patients tested through a coordinator-supported, standardized testing pathway completed the necessary testing steps, in less time, compared to usual care. These findings may inform institutions seeking to create effective population-wide testing programs for HCV and other conditions.